Persepsi Masyarakat Terhadap Ekosistem Daerah Aliran Sungai Ayung Menuju Sumberdaya Air Berkelanjutan - Sudarma, I Made; Widyantara, Wayan (Bumi Lestari, 2016)
The sustainability of watershed ecosystem functions in managing the water system can be achieved if the utilization pattern of their territories in accordance with the rules of conservation. A decrease in quantity and quality of the river water can be an indicator that condition of the watershed have been damaged. The destruction of the watershed ecosystem as a result of various causes will be able to threaten supply of sustainable water resources. The aim of this research is to determine and analyze the perceptions and behavior of upstream communities and governments about the function and role of water conservation and watershed in their behavior in the preservation of the watershed and its relationship with the current condition of the Ayung river. The study was conducted in the area upstream of Ayung river, which is in the Belok Sidan and Plaga Village, Petang, Badung, stake holder water users Ayung River such as PDAM, AMDK, rafting and farmers, as well as the government of Badung Regency that responsible for the management and conservation of Ayung River. Results of the study found that the public perception of the functions and benefits of watershed in the conservation of water resources classified in the category of high, but was followed by actions or attitudes in the medium category. There was no real relationship between perception and action, but the action affect current watershed conditions. The role and participation of stakeholders Ayung River water users were still relatively low in the preservation of the watershed, while the government's role classified as medium has not been done in an integrated among sectors and regions. From the results of this study it is recommended that the preservation of the Ayung river through various conservation action were integrated by involving communities upstream more active through the empowerment of local knowledge and improve their welfare. Government plays an important role in moving towards unity of this act.
Keywords: watershed; water; conservation; sustainable